Development of Children's Creative Activity in Preschool - Anna Klim-Klimaszewska (Ignatianum University Press, 2019)
An essential element of the teaching system, which is of vital importance, is the set of educational methods. A prominent place amongst these is occupied by those methods that develop creative activity; this is because the main element that results in the maximizing of the child's developmental chances is its creative activity. The article presents the following methods that actively develop the nursery school pupil's creativity: the project method, the construction of board games, Celestyn Freinet's techniques, Maria Montessori's method, Carl Orff's method of physical expression through actions, Alfred and Maria Kniess' method of rhythmical gymnastics, Weronika Sherborne's Developmental Movement, Josef Gottfrid Thulin's method of making stories through physical actions, Emil Jagues-Dalcroze's method, Edwin E. Gordon's method of developing the love of music, Bati Strauss' method of active listening to music, theatre, drama, music therapy, Maxwell Malz's method of forming a positive image of oneself, and the practise of creative visualization for children. The methods listed above are different ways of working with children that rely on releasing their free creative expression, in contrast to traditional teaching methods that oppose those methods that activate the educational process. They are educational and developmental methods for children who are at nursery school, and they facilitate unconstrained activeness and creation.